Does Corruption Promote Emigration? An Empirical Examination - Arusha Cooray; Friedrich Schneider (Institute for the Study of Labor (IZA), 2014)
This paper empirically investigates the relationship between corruption and the emigration of those with high, medium and low levels of educational attainment. The empirical results indicate that as corruption increases the emigration rate of those with high levels of educational attainment also increases. The emigration rate of those with middle and low levels of educational attainment, however, increases at initial levels of corruption and then decreases beyond a certain point. Splitting the sample by income inequality suggests that increased inequality reduces the ability to emigrate. The policy conclusion is, that government actions should focus on controlling corruption, which in turn would lead to funds being channeled more productively into education and also lead to a fall in inequality which would reduce emigration.
Keywords: O17; O5; D78; H2; H11; H26; 330; corruption; emigration; educational attainment; government expenditures; income inequality; labor markets